2012
DOI: 10.1111/j.1365-2648.2012.06084.x
|View full text |Cite
|
Sign up to set email alerts
|

What works: a realist evaluation case study of intermediaries in infection control practice

Abstract: The study provides theoretical threads of how intermediaries can be successful in promoting evidence use under certain contextual conditions. Further testing of the specific intermediary mechanisms uncovered in this study will contribute to understanding different approaches that work in infection control in embedding evidence in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 34 publications
(43 reference statements)
0
60
0
Order By: Relevance
“…They could also have provided greater supervision for unqualified nurses and been more proactive to ensure that ward areas were better serviced to promote a safe, clean environment with the necessary resources. Previous research has suggested that the presence of university teachers in clinical areas could encourage better compliance with IPC precautions by ward staff 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They could also have provided greater supervision for unqualified nurses and been more proactive to ensure that ward areas were better serviced to promote a safe, clean environment with the necessary resources. Previous research has suggested that the presence of university teachers in clinical areas could encourage better compliance with IPC precautions by ward staff 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This can be overcome with up-to-date e-learning packages 8 , while simulated patient care exercises in the clinical skills laboratory have been suggested as a way of helping student nurses grasp the complexity of clinical decisionmaking in relation to IPC 10 . The presence of university teachers in clinical areas has also been identified as a mechanism for encouraging compliance with IPC precautions by ward staff 11 . Student nurses have identified qualified nurses as important role models for key aspects of IPC 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have used RE to evaluate a range of programs including: nursing education (Stavropoulou & Stroubouki, 2014) (Brimdyr et al, 2012;Machin & Pearson, 2014); infection control interventions (Williams, Burton & Rycroft-Malone, 2012); the care of patients with dementia (Tolson& Schofield, 2012); and workplace culture (Wilson, McCormack & Ives, 2005). The authors' justifications (where provided) for using RE were: to capture the differing realities of a person's experience and the contextual factors that influenced their perceptions (Machin & Pearson, 2014); to tease out transferable lessons from interventions (Williams et al, 2012); to explore context factors (Tolson & Schofield, 2012); and to gain an in-depth exploration (Wilson et al, 2005).…”
Section: Realist Evaluation and Nursingmentioning
confidence: 99%
“…The authors' justifications (where provided) for using RE were: to capture the differing realities of a person's experience and the contextual factors that influenced their perceptions (Machin & Pearson, 2014); to tease out transferable lessons from interventions (Williams et al, 2012); to explore context factors (Tolson & Schofield, 2012); and to gain an in-depth exploration (Wilson et al, 2005).…”
Section: Realist Evaluation and Nursingmentioning
confidence: 99%
“…[261][262][263][264][265][266] However, a number of challenges have emerged concerning the operationalisation of each component of the CMO configuration. These challenges are discussed in the following four sections.…”
Section: Realist Inquirymentioning
confidence: 99%